2017
DOI: 10.1088/1757-899x/165/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Velocity Ballistic Impact on Pretensioned Carbon Fibre Reinforced Plastic (CFRP) Plates

Abstract: This work describes an experimental investigation of the pretensioned thin plates made of Carbon Fibre Reinforced Plastic (CFRP) struck by hemispherical and blunt projectiles at various impact velocities. The experiments were done using a gas gun with combination of pretension equipment positioned at the end of gun barrel near the nozzle. Measurements of the initial and residual velocities were taken, and the ballistic limit velocity were calculated for each procedures. The pretension target results in reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…From the 45-degree graph, the maximum value of the kinetic energy computed when 60 km/h velocity impact is applied is 178 kJ. The kinetic energy will decrease in an increasing of time and does not stop until the end of the simulation which is at 0.05 s as 2.90 kJ is the minimum value of the kinetic energy [14,15]. While, for 70-degree the maximum kinetic energy for the car frame is 178 kJ and decreases along the time of the simulation until reached the minimum value of 16.1 kJ.…”
Section: Results For Steel 321 Energy Balancementioning
confidence: 99%
“…From the 45-degree graph, the maximum value of the kinetic energy computed when 60 km/h velocity impact is applied is 178 kJ. The kinetic energy will decrease in an increasing of time and does not stop until the end of the simulation which is at 0.05 s as 2.90 kJ is the minimum value of the kinetic energy [14,15]. While, for 70-degree the maximum kinetic energy for the car frame is 178 kJ and decreases along the time of the simulation until reached the minimum value of 16.1 kJ.…”
Section: Results For Steel 321 Energy Balancementioning
confidence: 99%
“…Such models are present in literature for ductile materials such as the primary AA7010 and also for composites that behave in a brittle manner [27][28][29][30]43]. Using FEA, much more can be learned about the material in question such as its ballistic limit [31], oblique impact behaviour [32], ballistic response [33] and real life complex simulations [34] etc. However, to establish a numerical model, experimental data is required for validation [35].…”
Section: Introductionmentioning
confidence: 99%
“…A damage model characterized by the volume of impact damage was proposed, and the damage development and fragmentation of glass plates were divided into three stages: first, for a loading rate of low intensity and long impact duration, simple fragmentation occurred, where the initiation of cracks were observed at the same location of the micro-defect without crack branching; second, multistage fractures caused by the bifurcation of many cracks appeared, and radial and tangential cracks were formed; the final stage was to complete the perforation. For ductile materials, Kamarudin & Hamid (2017) carried out an experimental investigation on thin plates made of carbon fibre reinforced plastic (CFRP) impacted by hemispherical and blunt projectiles at various velocities. It was also observed that a hemispherical projectile split a target plate at a lower impact velocity compared with a flat projectile.…”
Section: Introductionmentioning
confidence: 99%